Bordering, dissolving, meeting regenerating - Bonny Cassidy (2021)
Cassidy writes from the perspective of a settler Australian poet, editor, critic, and academic about the tensions between an historically white Australian poetry culture and material solidarity with First Nations expressions of sovereignty. Responding to key arguments on solidarity by Bundjalung scholar Evelyn Araluen and settler ally Clare Land, Cassidy identifies specific examples of contemporary “white” poets who have attempted to define solidarity through their writing methods. She considers the industrial and cultural work to be done by fellow settler poets and readers in relation with sovereign voices.